2005
DOI: 10.1161/01.str.0000170635.45745.b8
|View full text |Cite
|
Sign up to set email alerts
|

Matched Case-Control Study on Factor V Leiden and the Prothrombin G20210A Mutation in Patients With Ischemic Stroke/Transient Ischemic Attack Up to the Age of 60 Years

Abstract: Background and Purpose-The role of the factor V Leiden mutation (FVL) and the G20210A mutation of the prothrombin (factor II [FII]) gene for arterial thrombosis is not clear. Methods-We investigated the prevalence of these mutations in 468 patients with an acute stroke or transient ischemic attack (TIA) before the age of 60 years and in a healthy control population individually matched for age and gender. We also analyzed interactions between the mutations, gender, standard vascular risk factors, and stroke ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 31 publications
(28 reference statements)
3
67
1
9
Order By: Relevance
“…Eighteen studies [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124] were conducted in the USA; nine [125][126][127][128][129][130][131][132][133] 61,[149][150][151] two in Canada; 152,153 and three in Australia. [154][155][156] Most studies were undertaken in a hospital/clinical 112,113,115,123,137,140,143,144,146,150,151 Four studies 61,107,128,145 reported data for atrial septal defect using TTEf and two 123,128 reported data for atrial septal defect using TTEh.…”
Section: Settingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eighteen studies [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124] were conducted in the USA; nine [125][126][127][128][129][130][131][132][133] 61,[149][150][151] two in Canada; 152,153 and three in Australia. [154][155][156] Most studies were undertaken in a hospital/clinical 112,113,115,123,137,140,143,144,146,150,151 Four studies 61,107,128,145 reported data for atrial septal defect using TTEf and two 123,128 reported data for atrial septal defect using TTEh.…”
Section: Settingsmentioning
confidence: 99%
“…Two studies 61,117 reported data for mitral valve regurgitation using TTEf and one study 119 reported data for mitral valve regurgitation using TTEh; eight studies 61,107,120,125,132,142,152,156 reported data for left atrial appendage thrombi using fundamental imaging and one study 120 used harmonic imaging. Left atrial thrombi data were reported in three studies 145,148,156 using TTEf and three studies 126,136,141 using TTEh; one study 138 reported data for right atrial thrombi using TTEf; three studies 122,124,130 reported TTEh and TTEf data for left ventricular thrombi; three studies 114,132,142 reported TTEf data for spontaneous echo contrast (SEC); four studies 118,152,154,155 reported TTEf data for left atrial SEC and one study 136 reported TTEh data for left atrial SEC; one study 154 reported data for left ventricular SEC with TTEf; two studies reported TTEf and TTEh data for left ventricular aneurysm; 108,135 two studies reported TTEh data for cardiac vegetations 149,153 and one study 149 reported TTEf data; one study 129 reported TTEf data for aortic valve stenosis; one study 61 reported TTEf data for mitral valve stenosis; two studies 111,147 reported TTEh data for mitral valve prolapse; and one study 148 reported TTEf data for atrial myxoma.…”
Section: Assessment Of Diagnostic Accuracymentioning
confidence: 99%
See 2 more Smart Citations
“…Varias mutaciones y polimorfismos se han descrito para este gen, y se ha propuesto el polimorfismo C677T como un factor de riesgo para la enfermedad vascular y la ateroesclerosis debido a la reducción de la actividad enzimática y a la elevación de los niveles de homocisteína en plasma (56)(57)(58)(59). En 1995, el grupo de Frosst identificó la sustitución de una citosina por una timina en el nucleótido 677, la cual convierte un residuo de alanina en valina, y se relaciona con la reducción de la actividad enzimática y el incremento de la termolabilidad de los extractos linfocitarios (57,60).…”
Section: Metilen-tetrahidrofolato Reductasaunclassified